Tunable electronic properties of InSe by biaxial strain: from bulk to single-layer. (25th September 2019) - Pham, Khang D; Vi, Vo T T; Thuan, Doan V; Phuong, Le T T; Hoa, Le T; Hieu, Nguyen V; Nguyen, Chuong V; Phuc, Huynh V; Jappor, Hamad R; Cuong, Nguyen Q; Hoi, Bui D; Hieu, Nguyen N
Abstract: In the present work, we consider the electronic properties of bulk and single-layer InSe using the density functional theory. Our calculations show that at the equilibrium state, the single-layer InSe is a semiconductor with an indirect energy bandgap of 1.382 1 eV, nearly twice the bandgap of bulk InSe. Focusing on the effect of biaxial strain ε b on electronic properties of single-layer InSe, our calculated results indicate that tensile biaxial strain changes slightly the valence subbands near Fermi level, while the band structure of the single-layer InSe depends tightly on the compressive biaxial strain. Also, the energy gap of the single-layer InSe depends almost linearly on the ε b . However, the energy gap tends to increase slowly when the large compressive biaxial strain is applied. We believe that the control of the energy gap of the single-layer InSe by strain engineering can be useful in its application in nanoelectromechanical systems and nanoelectronic devices.